Dwelling into service innovation management practices: a comparison between telecommunication industry in Malaysia and Bangladesh - Taghizadeh, Seyedeh Khadijeh; Rahman, Syed Abidur; Abdul Halim, Hasliza; Ahmad, Noor Hazlina (SAGE Publications, 2017)
In the multifaceted as well as vibrant telecommunications industry, service innovation management is a relatively new paradigm, which has attracted the attention of scholars and practitioners.Thus, this study embarks on to compare the practices of service innovation management between Malaysia and Bangladesh telecommunications industry.The strategy, process, organization, tool/technology and system (SPOTS) model with 26 indicators was employed to compare the management practices among these two countries.A total of 176 managers (98 from Malaysia and 78 from Bangladesh) participated in this research through survey questionnaires. An independent-samples t-test was conducted to compare the 26 indicators on management practices for Malaysian and Bangladesh telecommunications industry.The findings indicated that the management practices were ope rationalized differently in these two countries.Bangladesh put more emphasis on each of the innovation management practices when compared to Malaysia.It indicates that innovation management is practiced more in the country where the market is in the process of development.The results enable the firms to better compete in an environment which requires innovative changes and global discipline.In fact, the findings provide guidelines for the service sectors in both countries in terms of implementation of innovative enterprises, especially in Bangladesh where innovation is the basis for survival.